Capsule Size Alters the Timing of Metabolic Alkalosis Following Sodium Bicarbonate Supplementation - Middlebrook, India; Peacock, Joe; Tinnion, Daniel J.; Leach, Nicholas K.; Hilton, Nathan P.; Saunders, Bryan; Sparks, S. Andy; Mc Naughton, Lars R. (Frontiers in Nutrition, 2021)
Introduction: Sodium bicarbonate (NaHCO3) is a well-established nutritional ergogenic aid that is typically ingested as a beverage or consumed in gelatine capsules. While capsules may delay the release of NaHCO3 and reduce gastrointestinal (GI) side effects compared with a beverage, it is currently unclear whether the capsule size may influence acid–base responses and GI symptoms following supplementation. Aim: This study aims to determine the effects of NaHCO3 supplementation, administered in capsules of different sizes, on acid–base responses, GI symptoms, and palatability. Methods: Ten healthy male subjects (mean ± SD: age 20 ± 2 years; height 1.80 ± 0.09 m; weight 78.0 ± 11.9 kg) underwent three testing sessions whereby 0.3 g NaHCO3/kg of body mass was consumed in either small (size 3), medium (size 0), or large (size 000) capsules. Capillary blood samples were procured pre-ingestion and every 10 min post-ingestion for 180 min. Blood samples were analyzed using a radiometer (Radiometer ABL800, Denmark) to determine blood bicarbonate concentration ([HCO3-]) and potential hydrogen (pH). GI symptoms were measured using a questionnaire at the same timepoints, whereas palatability was recorded pre-consumption. Results: Capsule size had a significant effect on lag time (the time [HCO3-] changed, Tlag) and the timing of peak blood [HCO3-] (Tmax). Bicarbonate Tlag was significantly higher in the large-sized (28 ± 4 min) compared with the small-sized (13 ± 2 min) capsules (P = 0.009). Similarly, Tmax was significantly lower in the small capsule (94 ± 24 min) compared with both the medium-sized (141 ± 27 min; P < 0.001) and the large-sized (121 ± 29 min; P < 0.001) capsules. The GI symptom scores were similar for small-sized (3 ± 3 AU), medium-sized (5 ± 3 AU), and large-sized (3 ± 3 AU) capsules, with no significant difference between symptom scores (F = 1.3, P = 0.310). Similarly, capsule size had no effect on palatability (F = 0.8, P = 0.409), with similar scores between different capsule sizes. Conclusion: Small capsule sizes led to quicker Tlag and Tmax of blood [HCO3-] concentration compared to medium and large capsules, suggesting that individuals could supplement NaHCO3 in smaller capsules if they aim to increase extracellular buffering capacity more quickly.